Checkpoint inhibitor use in two heart transplant patients with metastatic melanoma and review of high-risk populations. (26th October 2018) - Grant, Michael J; DeVito, Nicholas; Salama, April K S
Due to the unique side-effect profile of immune checkpoint inhibitors (ICIs), groups of patients deemed to be at high risk of complications were excluded from trials that proved the efficacy and safety of these agents in patients with various malignancies. Among these excluded patients were those with prior solid organ transplantation, chronic viral infections and pre-existing autoimmune diseases including paraneoplastic syndromes. We present follow-up on a patient from a previously published case report with an orthotopic heart transplantation who was treated with both cytotoxic T-lymphocyte antigen 4 and PD-1 inhibition safely, without organ rejection. Additionally, we describe the case of a patient with a cardiac allograft who also did not experience organ rejection after treatment with pembrolizumab. Through smaller trials, retrospective analyses, case series and individual case reports, we are accumulating initial data on how these agents are tolerated by the aforementioned groups. Our survey of the literature has found more evidence of organ transplant rejection in patients treated with PD-1 inhibitors than those treated with inhibitors of cytotoxic T-lymphocyte antigen 4. Patients with chronic viral infections, especially hepatitis C, seem to have little to no risk of treatment-related increase in serum RNA levels. The literature contains few documented cases of devastating exacerbations of pre-existing autoimmune disease during treatment with ICIs, and flares seem to be easily controlled by immunosuppression in the vast majority of cases. Last, several cases allude to a promising role for disease-specific antibodies and other serum biomarkers in identifying patients at high risk of developing certain immune-related adverse events, detecting subclinical immune-related adverse event onset, and monitoring treatment response to immunosuppressive therapy in patients treated with ICIs. Though these excluded populations have not been well studied in randomized placebo-controlled trials, we may be able to learn and derive hypotheses from the existing observational data in the literature.